2018
DOI: 10.3892/ol.2018.9862
|View full text |Cite
|
Sign up to set email alerts
|

Expression profile and biological function of miR‑455‑5p in colorectal carcinoma

Abstract: Underexpression of microRNA-455-5p (miR-455-5p) in medullary thyroid carcinoma, melanoma, gastric cancer and additional cancer types has been reported, which may be associated with carcinoma development. The present study aimed to evaluate the expression profile and biological role of miR-455-5p in colorectal carcinoma. Carcinoma tissues and adjacent tissue specimens from 40 patients with colorectal cancer were randomly collected. Reverse transcription-quantitative polymerase chain reaction (RT-qPCR) analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…miR-455-5p is usually considered as a tumor suppressor since may studies show that its level is down-regulated in cancer tissues. For instance, in colorectal cancer, expression of miR-455-5p is sharply reduced and overexpression of miR-455-5p greatly inhibited colorectal cancer cell proliferation and migration [ 11 ]. In breast cancer, miR-455-5p has similar tumor suppressor effect [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…miR-455-5p is usually considered as a tumor suppressor since may studies show that its level is down-regulated in cancer tissues. For instance, in colorectal cancer, expression of miR-455-5p is sharply reduced and overexpression of miR-455-5p greatly inhibited colorectal cancer cell proliferation and migration [ 11 ]. In breast cancer, miR-455-5p has similar tumor suppressor effect [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…By targeting CXCL12, circPVT1/miR-455-5p strongly affects MTC progression. Many other targets of miR-455-5p have been reported, such as galectin-9 and PIK3R1 and these interactions have been implicated in cancer development [ 11 , 50 ]. It will be interesting to examine whether those signaling pathways are involved in MTC as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PVT1 seems to specifically bind to miR-455-5p (Figure 6). This miRNA is frequently downregulated in colorectal tumors and acts predominantly as a tumor suppressor element by targeting phosphoinositide-3-kinase regulatory subunit 1 (PIK3R1) and Runt-related transcription factor 2 (RUNX2), both crucial for the development of tumors (72,130,131) (Figure 5). An equivalent tumor suppressor role has been attributed to miR-455 in gastric tumorigenesis (132,133).…”
Section: Mir-455mentioning
confidence: 99%
“…Interestingly, miR‐455‐5p was originally believed to be only a tumor suppressor 37 . However, increasing evidence has shown that miR‐455‐5p can be used as a prognostic indicator for gastrointestinal cancer, 31,38 liver cancer, 39 pancreatic cancer, 43 lung cancer, 32 breast cancer, 29 and prostate cancer 42 . In addition, miR‐455‐5p has been shown to play an anti‐inflammatory role in the immune system 26 .…”
Section: Discussionmentioning
confidence: 99%